Burst Error Enumeration of m-Array Codes over Rings and Its Applications (European Journal of Pure and Applied Mathematics, 2010)
Enumerating burst errors enables to obtain bounds on parameters of codes. Recently, Jain in[5] established a Reiger’s type bound for burst error correcting matrix codes over finite fields with respect to a non Hamming metric. Here, we extend these results to array codes over finite rings. Further, we also introduce a new constructive method for counting burst errors that avoids solving Diophantine inequalities in order to compute burst errors for each given weight. Finally, we apply our results on establishing some bounds for array codes over finite rings.